Application of ICF classification system in functional assessment of children with spinal muscular atrophy - O.V. Nazar; O.I. Hurzhii (Group of Companies Med Expert, LLC, 2022)
Spinal muscular atrophy (SMA) is a rare genetic inherited neuromuscular disease that requires a comprehensive multidisciplinary approach to diagnosis and treatment. Purpose - to provide a review of scientific works on comprehensive care for children with SMA according to the principles of the International Classification of Functioning, Disability and Health (ICF), standardized tools for assessing the functional status of the patient. Materials and methods. The article presents the data of the literature review on the use of ICF principles in the organization of care for children with SMA, the use of standardized tools for assessing the functional status of the patient. Review and discussion. The implementation of the IСF in daily practice helps to improve the rehabilitation aid to children with SMA. Using the philosophy of the ICF, physicians began to comprehensively assess the health of the child, to estimate the functionality of the child using standardized tools, to form rehabilitation goals in accordance with the functional capabilities of the child, to determine environmental factors which do not allow the child to fully realize their rehabilitation potential. Conclusions. ICF makes it possible to determine of all aspects of the life of a child with SMA and to determine the impact of environmental factors on its level of functioning. According to ICF principles it is necessary to use standardized tools to assess the health status and the functional activity of a child with SMA, for evaluating the effectiveness of rehabilitation. No conflict of interests was declared by the authors.